In Search of Teaching Quality of EFL Student Teachers through Teaching Practicum: Lessons from a Teacher Education Program - Siti Nurul Azkiyah (University of Ljubljana, 2017)
This study was intended to investigate the teaching quality of student teachers when they conducted their teaching practicum. Teaching quality is conceptualised based on eight classroom factors (orientation, structuring, modelling, application, questioning, building classroom as a learning environment, assessment, and time management) of the dynamic model, which have previously been found to affect student outcomes. The study used a mixed-methods design: a survey on students’ perceptions of the teaching quality of their teacher (student teachers) and classroom observation. The study was conducted in Tangerang Selatan, Indonesia, involving English as a Foreign Language (EFL) student teachers in the English Education Program, Syarif Hidayatullah State Islamic University, Indonesia and 199 students of three different schools. The findings revealed that the student teachers did not yet practice the classroom factors of the dynamic model. Some recommendations include incorporating the classroom factors of the dynamic model in the curriculum or syllabus related to pedagogical skills to better prepare teachers in the future. It is also beneficial to study the possibility of sending student teachers to school earlier not only for the teaching practicum but also for other relevant purposes.